Improving Student Learning Outcomes In Lessons Of History Of Islamic Civilization Through The Application Of Bingo Strategies - Widiani, Desti; Jiyanto, Jiyanto (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Abstract. This article is a field research using the